2014
DOI: 10.1155/2014/381976
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Bufei Yishen Formula in a Rat Chronic Obstructive Pulmonary Disease Model

Abstract: Bufei Yishen Formula (BYF) has been used for centuries in Asia to effectively treat patients with chronic obstructive pulmonary disease (COPD). This study established a COPD animal model in rats, wherein three groups (control, COPD, and BYF) were used to evaluate the mechanism(s) and curative effect of BYF. Pulmonary function and histomorphology demonstrated that BYF had an evident effect on COPD. Gene microarray was then exploited to analyze the effects of BYF on COPD. ClueGO analysis of differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…All herbs were decocted with water, steam sterilized, and brought to a final concentration of 0.6 g/mL. BYF has been described in a previous study [ 13 ] and a Chinese patent (number 2011101175781).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All herbs were decocted with water, steam sterilized, and brought to a final concentration of 0.6 g/mL. BYF has been described in a previous study [ 13 ] and a Chinese patent (number 2011101175781).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that a traditional Chinese medicine (TCM), Bufei Yishen Formula (BYF), had a curative effect on COPD, and the molecular mechanisms of its effect on COPD were investigated using transcriptomics (microarray analysis). We found that BYF treatment could significantly improve pulmonary function and lung tissue pathology of COPD rats by reducing the expression level of inflammation-related interleukins [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has confirmed that such granules could also improve COPD patient self-efficacy and satisfaction [30]. The dramatic and long-term effects of BY on decreasing inflammatory responses, reducing pulmonary pathological impairment, and airway remodeling have been shown in a COPD rat model [31][32][33][34].…”
Section: Introductionmentioning
confidence: 85%
“…In addition to Western medicine, traditional Chinese herbal medicine (TCHM) has long been used for the clinical treatment of COPD (15,16) and the mechanisms underlying the effects of TCHM on COPD therapy have been widely studied in pre-clinical animal models of COPD (17,18). In this study, TCHM such as Bufei Jianpi, Bufei Yishen and Yiqi Zishen granules, and Liuweibuqi capsule have been demonstrated to effectively improve lung function, increase skeletal muscle strength, bone mass density and bone mineral content, and reduce airway inflammation through different mechanisms, including the inhibition of inflammatory cytokines, regulation of matrix metalloproteinases (MMPs) and their biological inhibitors (tissue inhibitors of MMPs), and modulation of the transforming growth factor-β1/Smad signal pathway (17)(18)(19)(20)(21)(22). Moreover, it has been shown that glucocorticoids used in combination with certain TCHMs have a marked effect in the prevention and treatment of COPD (23)(24)(25)(26)(27) or asthma (28).…”
Section: Introductionmentioning
confidence: 99%